PENDEKATAN SETS (SCIENCE, ENVIRONMENT, TECHNOLOGY, AND SOCIETY) DALAM PEMBELAJARAN REDOKS PADA SISWA KELAS X MADRASAH ALIYAH NEGERI LIMBOTO - Umar, Lisdawati N.; Isa, Ishak; Bialangi, Nurhayati (Jurnal Entropi, 2009)
The research is experiment research that aimed to prove the different of students achievement that was taught by using SETS approach and by conventional significantly at MAN Limbotos students. The population were students of XA class, XB class and XC class of MAN Limboto in 2008/2009 academics years that consisted of 86 students. The sample was students of XA class and XC class that consisted of 50 students. The sample was taken by using Cluster Random Sampling technique. The instruments in collecting the data was essay test that validity and reliability had tested before. Method of data analyses were normality test, homogenity test and hypothesis test. At hypothesis test, it got tcount = 2.322, while ttable = 1,711. The result showed that students achievement that was taught by using SETS approach is better than students achievement that was taught by using conventional in Oxidation and Reduction Reaction lesson.